Flight MH17, Ukraine and the new Cold War : Prism of disaster - Pijl, Kees van der (Geopolitical economy., 2018)
On 17 July 2014 Malaysian Airlines Flight MH17 was shot down amid unrest in Ukraine, a conflict that led to a NATO-Russia standoff and the onset of a new period of East-West confrontation. This is the first scholarly work on the Ukrainian unrest and the tragic downing of MH17. It offers an analysis that challenges the Western consensus surrounding these events, emphasising the geopolitical and economic context of the West's standoff with Russia, the BRICS bloc, and the struggles over the EU's energy supply. Based on previously unpublished government and NATO documents as well as a wide array of sources this book offers an analysis of global political economy and contemporary debates about Russia and East-West relations.